(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Lip prints and bloodstains may be left behind in many crime scenes and may reveal the identity of the victim and the suspected person. This study was aimed to investigate the inheritance pattern of lip prints and blood groups among parents and their offspring in the Javanese population. 105 subjects from 25 Javanese family frames participated in this study. Lips print pattern was recorded and analyzed according to Suzuki and Tsuchihashi classification. A blood group test was also performed for each subject. The statistical analysis carried out using IBM® SPSS® Statistics version 23.0 (IBM, Armonk, New York, USA). The results of this study revealed that type II was the predominant pattern of lip prints among the Javanese population (34.3%). Blood group A was the predominant type in subjects with lip prints type II (15%). The result also shows that the lip prints pattern in girls tends to be inherited from the mother. However, the inheritance of lip prints pattern in boys couldn’t be determined precisely. The heritability of lip prints pattern was observed between parents and their offspring. Also, there was a tendency of blood groups to have a certain pattern of lip prints.